Estudio microestructural de la madera mediante tomografías de rayos-X - Rivera Ramos, Juan Gabriel (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
The wood from forest plantations aimed at providing a sustainable supply of raw material is essential for the timber industry in Mexico. The cellulose companies or of boards for the construction have established crops with hardwood species, awakening the interest for their use as solid wood. However, the wood of young trees from fast-growing plantations has lower-quality technological properties and the adequate control of these woods is not completely known, which allows them to be part of the timber and lumber supplying. This thesis analyzes the geometric characteristics of the 3D microstructure of two hardwoods species from forest plantations, using the X-ray microtomography in different resolutions for each one, in order to know the possible causes of the low quality. In addition, with this same technique, the changes in the same microstructure are analyzed before and after a heat treatment in the same coordinates of the test tube. The analysis of the geometrical characteristics in the microstructure of the Eucalyptus nitens Maiden, showed that the cells of the radial parenchyma are covered by an enveloping substance that extends between the tangential wall of the fibers, identified as a parenchymal tangential bulge in fibers (PTB), which observed indications of interfering in transverse efforts in the woody woven. Likewise, the deformation and permeability of the woody woven was evaluated, showing deformations and cracking in the wall of the fibers and microzones with confined porosity of more difficult access to permeability. Analyzes on the wood of Acacia mangium Willd showed that, after heat treatment, the wood presents marked degradation in the tangential wall of the fibers, on the substance identified as PTB. A slight compaction of the fiber wall was also observed, mainly in the radial face, and a contraction of the woody woven with a reduced porosity, especially in the fibers, since the vessels, unlike the rest of the woody woven, remained without reduction or deformation, maintaining its permeable capacity. It is concluded: The technique of X-ray microtomography solidly complements the studies to the microstructures of wood. The wood of Eucalyptus nitens presented characteristics that affect its quality. The heat treatment changes in Acacia mangium wood are related to the degradation of PTB in its cell wall.

La madera de plantaciones forestales encaminada a proveer un abastecimiento sostenido de materia prima es primordial para la industria maderera en México. Las empresas celulósicas o de tableros para la construcción han establecido cultivos con especies de latifoliadas, despertando el interés por su utilización como madera sólida. Sin embargo, la madera de árboles jóvenes provenientes de plantaciones de rápido crecimiento presenta propiedades tecnológicas de menor calidad y se desconoce del todo el control adecuado de estas maderas que le permitan formar parte de la madera en escuadría para abastecimiento. Esta tesis analiza las características geométricas de la microestructura en 3D de dos especies latifoliadas procedentes de plantaciones forestales, utilizando para ello la microtomografía de rayos- X en distinta resolución para cada una, a fin de conocer posibles causas de la baja calidad. Así mismo se analizan los cambios en la microestructura antes y después de un termotratamiento en iguales coordenadas de la probeta. El Eucalyptus nitens Maiden, mostró que las células del parénquima radial se encuentran cubiertas por una sustancia envolvente que se extiende entremedio de la pared tangencial de las fibras, identificada como abultamiento tangencial parenquimatoso en fibras (ATPF), la cual observó indicios de interferir en esfuerzos transversos en el tejido. Así mismo, se evaluó la deformación y permeabilidad del tejido, mostrando deformaciones y agrietamiento en la pared de las fibras y microzonas con porosidad confinada de más difícil acceso a la permeabilidad. Los análisis a la madera de Acacia mangium Willd mostraron que, después del termotratamiento, la madera presenta degradación acentuada en la pared tangencial de las fibras, sobre la sustancia identificada como ATPF. También se observó una ligera compactación de la pared de la fibra, mayormente en cara radial, y una contracción del tejido con una porosidad más reducida, sobre todo en las fibras, ya que los vasos, a diferencia del resto del tejido, permanecieron sin reducción ni deformación, manteniendo su capacidad permeable. Se concluye: La técnica de microtomografia de rayos-X complementa sólidamente los estudios a las microestructuras de la madera. La madera de Eucalyptus nitens presentó características que afectan su calidad. Los cambios por termotratamiento en la madera de Acacia mangium tienen relación con la degradación del ATPF en su pared celular.
Facultad de Ingeniería en Tecnología de la Madera. Maestría en Ciencias en Tecnología de la Madera
Keywords: info:eu-repo/classification/cti/7; FITECMA-R-M-2018-1157; TC rayos-X en madera; Microestructura de madera; Permeabilidad en madera; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1629